Reciclando e aprendendo: usando o lixo para construção de jogos pedagógicos - FARIAS, Lediana Serrão (2024)
This workof completionhas as its theme: RecyclingandLearning: Usingtrash tobuildeducational games, the sameisbibliographicalthereforefor its realizationwere consultedsomebibliographic sourcessuch asnewspapers, magazines, books, monographs, internetand someauthorson the subject. The samediscusses the use of"junk" for makingeducational gamesaslearning facilitator. Your goalis to showthe importance of recyclingin the educational processthrough the constructionof games withrecyclable materials, to raise awarenessand buildingvalues andproper attitudesin the environment. The gamesbuilt withrecycled materialsprovideexperiencesto childrenof reusingdisposable materials, "junk", as a pedagogical resourcewill bringthe development ofskillsandcapabilities. The survey resultsindicate thatthe child learnsexperiencing, experimenting, making discoveriesand acting, through the constructionof toysand games withrecyclables, the school canteach, in order topreparecitizensfrom early childhood educationto learnposturesrespect for nature. Whenearlymanawareof environmental issues, the possibility of obtaininggreaterrespectwill, through knowledgepeople canacquireconcepts thatare consistentwith the environmentbalanced.Enterthe gamesin education withthe useof wasteas well asleadthe child toa betterway of learningto acquireteachesrespect andlove for nature. The gameawakensin the childa greater interestin the processofteaching and learningthroughtoys andgamesrecyclablesmay discussvarious subjects.